2004
DOI: 10.17660/actahortic.2004.629.17
|View full text |Cite
|
Sign up to set email alerts
|

ESSENTIAL OIL COMPOSITION OF ALOYSIA TRIPHYLLA (L'HERIT) BRITTON LEAVES CULTIVATED IN BOTUCATU, SãO PAULO, BRAZIL

Abstract: The family Verbenaceae comprises about 175 genera and 2300 species, distributed in tropics and subtropics, mainly in temperate zone of southern hemisphere. The lemon verbena (Aloysia triphylla (L'Herit) Britton) is a perennial, bushy plant originally from South America. The essential oil of this plant is used in pharmaceutical, cosmetic and perfumery industry. Therapeutic properties include febrifuge, sedative, stomachical, diuretic, and antispasmodic activities. The present work aimed to identify the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Asekun et al (2007) reported that method of drying affected the oil composition of Mentha longifolia. In addition, the results are very similar to those of Figueiredo et al (2004) who reported that the total main components in lemon verbena essential oil were 1,8-cineole, geranial, limonene, linalool, and spathulenol, and represented more than 50 % from the total components in lemon verbena essential oil.…”
Section: Freshsupporting
confidence: 89%
See 1 more Smart Citation
“…Asekun et al (2007) reported that method of drying affected the oil composition of Mentha longifolia. In addition, the results are very similar to those of Figueiredo et al (2004) who reported that the total main components in lemon verbena essential oil were 1,8-cineole, geranial, limonene, linalool, and spathulenol, and represented more than 50 % from the total components in lemon verbena essential oil.…”
Section: Freshsupporting
confidence: 89%
“…Lemon verbena leaves contain high quality essential oil of lemon scent and its main constituents are limonene, spathulenol, geranial, citral, and linalool. The essential oil of lemon verbena contains several physiologically active substances, and is used as antispasmodic, antipyretic, sedative, stomachic, and diuretic, (Keville, 1999 andFigueiredo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of Aloysia polystachya are used, in Argentina, for respiratory diseases (colds and cough), gastrointestinal pain (Filipoy, 1994), as antiemetic (Martinez Crovetto, 1981) and sedative remedy (Del Vitto et al, 1997). Therapeutic actions of other species of Aloysia (i.e., Aloysia triphilla) include febrifuge, sedative, stomachic, diuretic and antispasmodic activities (Oliveira de Figueiredo et al, 2002). However, we found no scientific references or experimental evaluation regarding its central nervous system activity, as well as informations about the toxicity of Aloysia polystachya.…”
Section: Introductionmentioning
confidence: 81%
“…The family Verbenaceae comprises about 175 genus and 2300 species, distributed in the tropics and subtropics, mainly in the temperate zone of Southern Hemisphere (Oliveira de Figueiredo et al, 2002). Mental ailments are heterogeneous diseases and will probably require a selected arsenal of drugs with different modes of action for successful treatment of their various manifestations (Baldessarini, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…De Figueiredo et al (2004), researched essential oil compounds, extracted from leaves Aloysia triphylla collected in Sao Paulo (Brazil). The compounds with the highest percentage are: geranial (29.54%), neral (27.01 %), limonene (15.93 %), geranyl acetate (4.0 %), geraniol (3.96 %) (De Figueredo et al,2004).…”
Section: Figure1: Image Aloysia Triphylla (L Her) Britton Plantmentioning
confidence: 99%